1997
DOI: 10.3109/08923979709038536
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Enhances Antibody Response in Rats

Abstract: The effects of dietary curcumin on three major types of immune function were examined in rats. Antibody (IgG) production, delayed-type hypersensitivity and natural killer cell activity were evaluated after 5 weeks of dietary exposure to 1, 20 or 40 mg/kg curcumin. The highest dose of curcumin significantly enhanced IgG levels. Rats receiving lower dietary concentrations (1 or 20 mg/kg) of curcumin were not different in IgG production from rats receiving no curcumin in their diet. Neither delayed-type hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 28 publications
1
24
1
1
Order By: Relevance
“…The highest doses of curcumin, significantly enhanced IgG levels. Neither delayedtype hypersensitivity nor natural killer cell activity was different from control values at any dietary concentration of curcumin [14]. Another significant study by Ram A et al, studied the effect of curcumin on airway hyperresponsiveness in sensitized guinea pigs and demonstrated by a constant volume body plethysmograph that curcumin significantly inhibited ovalbumin-induced airway constriction and airway hyperreactivity in guinea pigs [15].…”
Section: Discussionmentioning
confidence: 99%
“…The highest doses of curcumin, significantly enhanced IgG levels. Neither delayedtype hypersensitivity nor natural killer cell activity was different from control values at any dietary concentration of curcumin [14]. Another significant study by Ram A et al, studied the effect of curcumin on airway hyperresponsiveness in sensitized guinea pigs and demonstrated by a constant volume body plethysmograph that curcumin significantly inhibited ovalbumin-induced airway constriction and airway hyperreactivity in guinea pigs [15].…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric powder supplementation levels in the present experiment may not be optimal for enhancing immune responses in chickens. For instance, studies by South et al (1997) on rats showed that curcumin at a dose of 10 and 20 mg/kg body weight could not enhance the IgG levels in the NK cells, whereas a higher dose (40 mg/kg) did elevate IgG levels significantly. More importantly, none of the three doses of curcumin significantly enhanced either delayed-type hypersensitivity or NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exerts a number of effects at sites distal from the gastrointestinal tract at doses less than or equivalent to the 12 g/day maximum dose administered in Phase I human clinical trials (to enable rough comparisons, we calculate that 12 g/day is approximately equivalent to 2 % curcumin when administered in the diet (12 g/500 g diet); when administered by weight, it is approximately equivalent to 200 mg/kg body weight). For example, immunomodulatory effects of curcumin (e.g., release of ROS [13] and eicosinoids [209] from peritoneal macrophages, antibody response) were observed following treatment with 40 mg/kg curcumin in the diet [210] or by 30 mg/ kg introduced by gavage [13,209]. Dietary curcumin at 160 ppm also lowered oxidized proteins and IL-1b in the brains of a transgenic mouse model of Alzheimers disease [211].…”
Section: Safety and Pharmacologymentioning
confidence: 99%